(untitled) (Journal of Economic Research & Business Administration, 2016)
Today any country of the world won’t be able to provide sustained economic growth without attraction of investments. Considering world crisis, the competition for attraction of PII increases. Therefore the competent investment policy from the state is a major factor in the field of investment activity. Are shown to present the main tendencies for the last decade in article as world and across the nation. Advantages of Kazakhstan in comparison with other countries of the region in the field of attraction of investments were shown. The main actions of the government in the sphere of investment policy are also displayed.